FAKTOR-FAKTOR YANG MEMENGARUHI CUSTOMER LOYALTY KOPI KENANGAN DI JAKARTA - MUHAMMAD FAQIH NURHASAN; ARTON BRIYAN PRASETIO (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to examine and analyze the relationships among Perceived Quality, Customer Expectations, Customer Social Value, and Customer Emotional Value on Customer Loyalty, with Perceived Value and Customer Satisfaction as mediating variables among consumers of Kopi Kenangan in Jakarta. Perceived Value mediates the relationship between those four factors and Customer Satisfaction, while Customer Satisfaction mediates the relationship between Perceived Value and Customer Loyalty. The sampling technique employed is non-probability sampling using the purposive sampling method. A total of 260 respondents who met specific criteria participated in this study through an online questionnaire distributed via Google Form. The data were analyzed using the Structural Equation Modeling (SEM) approach with the help of WarpPLS 8.0 software, which is suitable for analyzing complex models and handling non-normal data distributions. The results of the study indicate that Perceived Quality, Customer Expectations, Customer Social Value, and Customer Emotional Value have a significant effect on Perceived Value. Furthermore, Perceived Value and Location significantly influence Customer Satisfaction. Ultimately, Customer Satisfaction has a significant impact on Customer Loyalty toward Kopi Kenangan in Jakarta.